Is There Any Relationship Between Hepatitis C Virus Infection and Skin Diseases ? - Al-Duliami , Abbas A; Al-Kiali , Khudiar Kh; Hasan, Abdul-Razak Sh (Diyala Journal of Medicine, 2019)
Background: Hepatitis C virus (HCV) has been associated with several extrahepatic conditions. Although a high prevalence of HCV infection was detected in patients with lichen planus, the pathogenetic potentials of HCV with skin diseases is still controversial. Aim: To determine the anti-HCV antibody seropositivity among patients with certain non-communicable skin diseases; lichen planus, psoriasis, alopecia areata, vitiligo, eczema, and urticaria. Patients and methods: Two hundred patients suffering from non-communicable skin disease were enrolled in this study which was conducted in Baquba for the period from 1st. November/2010 to 1st. July/2011. The patients were attending the Dermatology and Venereology Unit in the outpatient clinic of Baquba General Teaching Hospital. The patients group into 18 patients with lichen planus, 23 with psoriasis, 7 with vitiligo, 95 with eczema, 36 with chronic urticaria, and 21 with alopecia areata. The age range of the patients was (5-70) years. Additionally, 90 apparently healthy unpaid blood donors were included as control group. Anti-HCV antibody was detected by enzyme linked immunosorbant assay. Rsults: Only two patients were positive for anti-HCV antibody; one with lichen planus and another with eczema. All other patients with psoriasis, alopecia areata, vitiligo, and urticaria were negative for anti-HCV antibody. There was no significant association between HCV infection and skin diseases under study. Conclusion: No association between HCV infection and lichen planus, psoriasis, alopecia areata, vitiligo, eczema, and urticaria, probably due to low prevalence of HCV infection among general Iraqi people.